Genetic polymorphism of caprine stearoyl-coA desaturase (SCD) gene and their relationship with blood cholesterol, triglyceride and pre-weaning growth traits of mixed breeds of goats in southern Thailand - SUPAKORN, CHINA; PRALOMKARN, WINAI; TUMWASORN, SORNTHEP (The Indian Journal of Animal Sciences, 2016)
The present study attempts to identify genetic polymorphisms of stearoyl-coA desaturase (SCD) gene and their relationship with blood cholesterol, triglyceride and pre-weaning growth traits in a goat population in southern Thailand. Genetic variability in caprine SCD was analyzed in 290 animals belonging to several types of Thai native (TN), Anglo-nubian (AN), Boer (B) and Saanen (SA) breed crosses by PCR-SSCP and DNA sequencing. Four SNPs were identified in exon3 (A/G), exon5 (C/T), exon6 (C/G) and 3’untranslated region (3’UTR) (TGT deletion). Five haplotypes (A, B, C, D and E) were constructed. Haplotype frequency B was the highest (0.50) but haplotype frequency C was the lowest (0.01). Haplotype effect of SCD gene had influenced on blood cholesterol, triglyceride, weaning weight and growth rate. Individuals with haplotype C had significant lowest triglyceride, weaning weight and growth rate (P